Levantamento de hemopatógenos, ectoparasitas e soroprevalência de Toxoplasma gondii em gatos comunitários do Parque Municipal Américo Renné Giannetti de Belo Horizonte, Minas Gerais, Brasil - Mariana Cristina Sebastiani (2021)
The increase in the population of stray and feral cats (Felis silvestris catus) in urban areas can lead to a major problem for animal, environmental and human health. It is known that the Américo Renné Giannetti Municipal Park (PqMARG) located in the central region of Belo Horizonte, Minas Gerais, Brazil is an important green area of the city as it houses several species of wild animals and receives a large number of visitors. The place is also home to domestic animals, such as cats, which are socially organized in colonies and so far, there is no information on the health status of these animals in relation to parasitic agents such as vector- borne pathogens and Toxoplasma gondii. The main objective of this work is the detection of hemoprotozoa of the order Piroplasmida and Trypanosoma evansi, in addition to hemobacteria of the Anaplasmataceae family and Mycoplasma spp. and to determine the seroprevalence of Toxoplasma gondii in cats housed in the park. The study was a cross- sectional observational study carried out through the analysis of a bank of biological samples (ectoparasites, blood and serum) collected between the years 2015 to 2018. Specimens of fleas (Ctenocephalides felis felis and C. canis) and lice (Felicola subrostratus) were found and infections by Cytauxzoon felis, Trypanosoma evansi, Anaplasma platys and hemotropic mycoplasmas (Mycoplasma haemofelis, 'Candidatus Mycoplasma haemominutum and ‘Candidatus Mycoplasma turicensis’) were detected. The samples were negative for the primers used to detect Ehrlichia canis and Anaplasma phagocytophilum. The seroprevalence for T. gondii was 19,6% using IFA and 21% using ELISA. The results show that the circulation of agents transmitted by vectors occurs in cats from PqMARG, as well as seroprevalence data for T. gondii can serve as an indicator of environmental contamination by this agent of public health importance. The role of felines in the epidemiology of vector- borne-diseases still has many gaps and, therefore, further studies are needed to elucidate whether these animals can exert any pressure on the transmission chain of agents, especially those of human health importance.